Large-strain flexible ferroelectric composite film, preparation method thereof and electrostriction device
By using stacked structures and 0-3 type organic/inorganic composite film technology in electrostrictive materials, the problem of degradation of existing materials during large strains and repeated bending is solved, and an electrostrictive material with high flexibility, large strain and high bending resistance is achieved.
Patent Information
- Application Number
- CN202510321218.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-20
AI Technical Summary
It is difficult for existing electrostrictive materials to achieve large strain when they withstand large external forces, and their performance is easily degraded after repeated deformation cycles, making it difficult to meet the flexibility and multifunctional requirements of modern electronic equipment.
The structures of flexible piezoelectric polymer films, 0-3 organic/inorganic composite films, antiferroelectric films, 0-3 organic/inorganic composite films and flexible piezoelectric polymer films are prepared by sacrificial layer method and scraping film method and other technologies.
It realizes the characteristics of high flexibility and large electrostrain, and can adapt to the bending radius to the order of hundreds of microns to millimeters, can withstand thousands of bending times and has relatively stable electrical properties, avoiding the risk of fracture caused by repeated bending of traditional piezoelectric ceramic fiber composites.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrostrictive materials, and relates to a large-strain flexible ferroelectric composite film, a preparation method thereof, and an electrostrictor. Background Art
[0002] Electrostrictors have excellent performance in efficiently converting electrical energy into mechanical strain, and have significant advantages such as high-precision displacement, fast response, strong anti-fatigue property, and light weight, showing great potential in the driving field. The performance of electrostrictors depends on the electrostrictive strain characteristics of electrostrictive materials. Common materials such as PZN-PT relaxor ferroelectric single crystals have an electrostrictive strain of up to 1.7%. However, due to the brittle fracture characteristics of ceramics, they may undergo brittle fracture when subjected to a small external force, and cannot produce large elastic deformations like metals or some polymer materials, making it difficult to adapt to situations that require repeated deformations or large-strain driving. The molecular chains of flexible organic materials have certain flexibility and mobility, and can rearrange and orient under external stress, thus adapting to the deformation process, which can ensure the mechanical properties and stability of electrostrictors during high-precision displacement. However, flexible organic materials have a low Young's modulus, and flexible organic electrostrictive materials are prone to large deformations when subjected to a large external force, and cannot provide sufficient rigid support for the structure. Moreover, after experiencing multiple deformation cycles (such as repeated stretching, compression, or bending), the performance of flexible organic electrostrictive materials is prone to decline, and the fatigue life is relatively short. Therefore, in order to meet the requirements of flexibility and multifunctionality of modern electronic devices, it is very important to develop an electrostrictive material that simultaneously possesses excellent flexibility, large strain, excellent resistance to cyclic bending, and high stability.
[0003] Currently, the commonly used electrostrictive materials are mainly divided into piezoelectric ceramic fiber composites and PVDF-based flexible polymers and their modified composites. Commercial piezoelectric ceramic fiber composites are typical flexible driving materials. It usually embeds PZT ceramic fibers with a diameter of hundreds of micrometers in a polyimide film to construct a 1-3 type piezoelectric composite material, and its equivalent piezoelectric coefficient is usually about 400 pC / N, having good piezoelectric performance. Piezoelectric ceramic fiber composites usually have a thickness of about 300 micrometers, and the bending radius they can adapt to is usually at the centimeter level. Further bending is likely to cause the fracture of piezoelectric ceramic fibers. Therefore, piezoelectric ceramic fiber composites have good piezoelectric performance, but their flexibility is relatively poor, making it difficult to adapt to bending surfaces below the millimeter level and difficult to integrate with micro-nano devices. In addition, due to the lack of electrostrictive characteristics of the polyimide matrix, the strain output of piezoelectric ceramic fiber composites is usually much lower than 1%.
[0004] Organic films represented by polyvinylidene fluoride (PVDF) and its copolymer with trifluoroethylene (P(VDF-TrFE)) have good flexibility, but due to the molecular structure and interaction force of pure organic films, their strain is usually low, generally less than 3%. Usually, monomers (CFE, CTFE, VF, FA) are introduced by chemical modification to modify their molecular structure to increase their output strain. For example, Professor QM Zhang of Pennsylvania State University in the United States developed a new relaxor ferroelectric P(VDF-TrFE-CFE-FA) quaternary polymer (Science.2022, 375, 1418-1422) by introducing a small amount of special FA monomer into a specific ternary copolymer, achieving a strain of -5.8% under a relatively low electric field (80 MV / m). Through further optimization (Macromolecules, 2023, 56: 690-696.), in the P(VDF-TrFE-CFE-FA) quaternary polymer, the field-induced strain of the quaternary polymer containing 1.95 mol% FA can reach -3.3%, and the strain of the quaternary polymer of 50 MV / m can reach -7%. Professor QM Zhang of Pennsylvania State University also added CuPc nanoparticles (0-3 type) to P(VDF-TrFE) to induce the growth of the all-trans chain conformation (Nature, 2002, 419(6904): 284), which produced a strain of 1.9% under an electric field of 12 MV / m. In general, the output strain of flexible ferroelectric piezoelectric composites still needs to be improved. Summary of the invention
[0005] In order to solve the above problems of the prior art, the present invention provides a large-strain flexible ferroelectric composite film and a preparation method thereof and an electrostrictor, which have the characteristics of high flexibility and large electrostriction, and can adapt to bending radii of hundreds of microns to millimeters.
[0006] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a large-strain flexible ferroelectric composite film, comprising a flexible piezoelectric polymer film, a 0-3 type organic / inorganic composite film, an antiferroelectric film, a 0-3 type organic / inorganic composite film and a flexible piezoelectric polymer film stacked in sequence; wherein the flexible piezoelectric polymer film is a film formed by a relaxor ferroelectric polymer, the antiferroelectric film is a film formed by an antiferroelectric material, and the 0-3 type organic / inorganic composite film is a film formed by a composite of the relaxor ferroelectric polymer and the antiferroelectric material.
[0007] Preferably, the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is PbZrO3.
[0008] Preferably, the relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3.
[0009] Preferably, the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3; or, the relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is PbZrO3.
[0010] Preferably, the thicknesses of the flexible piezoelectric polymer film, the 0-3 type organic / inorganic composite film, and the antiferroelectric film are 10~30 μm, 30~100 nm, and 100~400 nm, respectively.
[0011] In a second aspect, the present invention provides a method for preparing the large-strain flexible ferroelectric composite film, including: S1, preparing a self-supporting antiferroelectric film by a sacrificial layer method, and transferring the antiferroelectric film onto a PDMS stamp; S2, preparing a flexible piezoelectric polymer film by a doctor blade method; S3, spin-coating a 0-3 type organic / inorganic composite film on the surface of the flexible piezoelectric polymer film, transferring the antiferroelectric film onto the surface of the 0-3 type organic / inorganic composite film by using the PDMS stamp, heating to peel off the PDMS stamp, and hot pressing; S4, spin-coating a 0-3 type organic / inorganic composite film on the surface of the antiferroelectric film obtained in S3, then preparing a flexible piezoelectric polymer film by a doctor blade method, and hot pressing to obtain the large-strain flexible ferroelectric composite film.
[0012] Preferably, S1 specifically includes: Depositing a sacrificial layer on a substrate by pulsed laser deposition; Depositing an antiferroelectric film on the sacrificial layer by pulsed laser deposition; Attaching the PDMS stamp to the surface of the antiferroelectric film, and removing the sacrificial layer by wet etching, so that the PDMS stamp carries the antiferroelectric film and detaches from the substrate.
[0013] Preferably, in S3 and S4, the preparation method of the 0-3 type organic / inorganic composite film is: preparing a solution of a relaxor ferroelectric polymer, adding nanoflour of an antiferroelectric material into the solution of the relaxor ferroelectric polymer, stirring, and ultrasonically dispersing to obtain a mixed solution of 0-3 type organic / inorganic composite; spin-coating the mixed solution of 0-3 type organic / inorganic composite on the surface of the flexible piezoelectric polymer film or the surface of the antiferroelectric film to prepare a 0-3 type organic / inorganic composite film.
[0014] Preferably, in S3 and S4, the hot pressing conditions are as follows: the temperature is 150 - 200 °C, the pressure is 1 - 3 Pa, and the vacuum degree is 0.1 - 1 Pa.
[0015] In a third aspect, the present invention provides an electrostrictor, comprising an electrostrictive material, wherein the electrostrictive material is the large-strain flexible ferroelectric composite film as described above, and a metal electrode is deposited on the outer side surface of the flexible piezoelectric polymer film in the large-strain flexible ferroelectric composite film.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The composite film provided by the present invention is composed of an organic material film and an inorganic material film, and can exert the synergistic effect of the organic material and the inorganic material in the composite material to enhance the strain output. The ionic displacement and lattice distortion of the inorganic material increase the electrostrictive strain inside it, generating a strong interfacial pressure to regulate the conformational transformation of the high electrostrictive characteristics in the organic material, thereby promoting the improvement of the large-strain output of the composite material. Secondly, introducing a 0-3 type organic / inorganic composite film can modify the organic / inorganic interface (i.e., the interface between the flexible piezoelectric polymer film and the antiferroelectric film), and improve the problem of weak bonding force between the flexible piezoelectric polymer film and the antiferroelectric film. At the same time, introducing a 0-3 type organic / inorganic composite film transition layer can alleviate the problem of large difference in Young's modulus at the organic / inorganic interface and avoid the problem of easy cracking of the composite film during repeated bending, significantly enhancing the bending resistance performance of the composite film. The relatively high Young's modulus is also beneficial for achieving large-strain output. In addition, the composite film of the present invention can adapt to a bending radius ranging from several hundred micrometers to the millimeter level, can withstand thousands of bendings and has relatively stable electrical properties, avoiding the fracture risk caused by repeated bending of traditional piezoelectric ceramic fiber composites. Therefore, the composite film of the present invention has the characteristics of high flexibility and large electrostrictive strain. Description of the Drawings
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0018] Figure 1 It is a flowchart of the preparation method of the large-strain flexible ferroelectric composite film of the present invention; Figure 2 It is a cross-sectional scanning electron microscope image of the large-strain flexible ferroelectric composite film in the first embodiment of the present invention; Figure 3 It is the electrostrictive strain output of the large-strain flexible ferroelectric composite film in the first embodiment of the present invention; Figure 4This is the electrostrain output after repeated bending of the large-strain flexible ferroelectric composite film in the first embodiment of the present invention. Specific Embodiments
[0019] The following specific examples illustrate the embodiments of the present invention. Those skilled in the art can easily understand the other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0020] It should be noted that the process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art.
[0021] It should be noted that the terms "comprising" and "having" and any variations thereof are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or device comprising a series of steps or units is not necessarily limited to those clearly listed steps or units, but may include other steps or units not clearly listed or inherent to these processes, methods, products, or devices. Moreover, unless otherwise stated, the numbering of each method step is only a convenient tool for identifying each method step, rather than limiting the arrangement order of each method step or the scope in which the present invention can be implemented. The change or adjustment of their relative relationship, without substantial change in technical content, should also be regarded as the scope in which the present invention can be implemented.
[0022] The large-strain flexible ferroelectric composite film described in the present invention includes a flexible piezoelectric polymer film, a 0-3 type organic / inorganic composite film, an antiferroelectric film, a 0-3 type organic / inorganic composite film, and a flexible piezoelectric polymer film stacked in sequence; wherein, the flexible piezoelectric polymer film is a film formed by a relaxor ferroelectric polymer, the antiferroelectric film is a film formed by an antiferroelectric material, and the 0-3 type organic / inorganic composite film is a film formed by the composite of the relaxor ferroelectric polymer and the antiferroelectric material.
[0023] In some possible embodiments, the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is PbZrO3.
[0024] In some possible embodiments, the relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3.
[0025] In some possible embodiments, the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3.
[0026] In some possible embodiments, the relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is PbZrO3.
[0027] In some possible embodiments, the thicknesses of the flexible piezoelectric polymer thin film, 0-3 type organic / inorganic composite thin film, and antiferroelectric thin film are 10-30 μm, 30-100 nm, and 100-400 nm, respectively.
[0028] The method for preparing the large-strain flexible ferroelectric composite film of the present invention includes: S1. Prepare a self-supporting antiferroelectric thin film by the sacrificial layer method, and transfer the antiferroelectric thin film onto a PDMS stamp; S2. Prepare a flexible piezoelectric polymer thin film by the doctor blade method; S3. Spin-coat a layer of 0-3 type organic / inorganic composite film on the surface of the flexible piezoelectric polymer thin film, then use the PDMS stamp to transfer the antiferroelectric thin film onto the surface of the 0-3 type organic / inorganic composite film, heat to peel off the PDMS stamp, and perform hot pressing; S4. Spin-coat a layer of 0-3 type organic / inorganic composite thin film on the surface of the antiferroelectric thin film obtained in S3, then prepare a flexible piezoelectric polymer thin film by the doctor blade method, and perform hot pressing to obtain the large-strain flexible ferroelectric composite film.
[0029] In the present invention, a layer of 0-3 type organic / inorganic composite film is prepared by spin-coating to perform surface modification on the flexible piezoelectric polymer thin film, so as to match the organic / inorganic interface between the flexible piezoelectric polymer thin film and the antiferroelectric thin film, and improve the problem of weak bonding force between the flexible piezoelectric polymer thin film and the antiferroelectric thin film; at the same time, by matching the organic / inorganic interface and reconciling the difference in Young's modulus of the organic / inorganic interface, the problem that the composite film is prone to cracking during repeated bending can be avoided, the bending resistance performance of the composite film is significantly enhanced, and large-strain output is achieved by virtue of the high Young's modulus.
[0030] In the above preparation method of the present invention, S1 specifically includes: Deposit a sacrificial layer on the substrate by pulsed laser deposition; Deposit an antiferroelectric thin film on the sacrificial layer by pulsed laser deposition; Attach the PDMS stamp to the surface of the antiferroelectric thin film, and remove the sacrificial layer by wet etching. The PDMS stamp carries the antiferroelectric thin film away from the substrate.
[0031] In the above preparation method of the present invention, in S3 and S4, the preparation method of the 0-3 type organic / inorganic composite film is as follows: prepare a solution of a relaxor ferroelectric polymer, add nanoflakes of an antiferroelectric material to the solution of the ferroelectric polymer, stir, and disperse ultrasonically to obtain a 0-3 type organic / inorganic composite mixed solution; spin-coat the 0-3 type organic / inorganic composite mixed solution on the surface of a flexible piezoelectric polymer film or an antiferroelectric film to prepare a 0-3 type organic / inorganic composite film.
[0032] Among them, the nanoflakes of the antiferroelectric material are prepared by a sol-gel method.
[0033] On the outer side of the flexible piezoelectric polymer film in the large-strain flexible ferroelectric composite film of the present invention, a patterned metal electrode (such as Au, Pt, Ag, etc.) is deposited by physical vapor deposition technology in combination with a stainless steel mask template, and a flexible driving device with large strain can be assembled.
[0034] Example 1: Preparation of PbZrO3 / P(VDF-TrFE-CFE) flexible ferroelectric composite film Reference Figure 1 , including the following steps: (1) Prepare a high-quality PbZrO3 self-supporting antiferroelectric film by the sacrificial layer method.
[0035] (1-1) Pretreat the substrate: sequentially place the (001)-oriented SrTiO3 single crystal substrate into acetone, alcohol, and deionized water, ultrasonically clean each for 5 minutes, and dry with nitrogen; (1-2) Deposit the sacrificial layer: deposit the sacrificial layer Sr3Al2O6 on the SrTiO3 single crystal substrate by pulsed laser deposition, with a laser energy of 0.9 W, a laser frequency of 3 Hz, a deposition temperature of 800 °C, an oxygen pressure of 20 Pa, and the thickness of the deposited sacrificial layer film is about 50 nm; (1-3) Deposit the PbZrO3 antiferroelectric film: deposit a PbZrO3 single crystal film on the sacrificial layer by pulsed laser deposition, with a laser energy of 0.6 W, a frequency of 5 Hz, a deposition temperature of 575 °C, an oxygen pressure of 20 Pa, and prepare an antiferroelectric film with a thickness of 100-400 nm by controlling the growth time, and the Young's modulus is about 60-80 GPa; (1-4) Attach a PDMS stamp to the surface of the antiferroelectric film, and then soak it in deionized water at room temperature for 12 h. After the Sr3Al2O6 sacrificial layer dissolves naturally in water, the PDMS stamp carries the antiferroelectric film and naturally detaches from the SrTiO3 substrate; (2) Prepare a P(VDF-TrFE-CFE) flexible piezoelectric polymer film by the doctor blade method to obtain a flexible piezoelectric polymer film with a thickness of about 20 μm.
[0036] (2-1) Preparation of P(VDF-TrFE-CFE) solution: Weigh commercial P(VDF-TrFE-CFE) particles and put them into N,N-dimethylformamide (DMF) solvent, stir and dissolve for 12 h to fully dissolve P(VDF-TrFE-CFE) in the solvent, forming a uniform and stable solution with a concentration of 0.1 g / ml. Among them, the stirring speed is 120 rpm to avoid introducing too many bubbles; (2-2) Preparation of flexible piezoelectric polymer film by blade coating method: Adjust the height of the blade to 40 μm. At room temperature, pour the P(VDF-TrFE-CFE) solution obtained in step (2-1) evenly onto a glass plate of 15 cm×10 cm, with a blade speed of 1 cm / s, and then dry it at 70 °C for 20 minutes to remove most of the solvent. After the solvent has basically evaporated, transfer the glass plate into an oven and dry it at 135 °C for 1.5 h to completely evaporate the solvent. Then, raise the temperature to 152 °C to improve the crystallinity and keep it at this temperature for 0.5 h, and then quench it in deionized water at room temperature to obtain a P(VDF-TrFE-CFE) flexible piezoelectric polymer film with a thickness of about 20 μm and a Young's modulus of about 2 GPa.
[0037] (3) Prepare PbZrO3 nanopowder by sol-gel method, and then compound it with P(VDF-TrFE-CFE) solution to prepare a 0-3 type organic / inorganic composite mixed solution.
[0038] (3-1) Preparation of PbZrO3 precursor solution: Use the 2MOE (ethylene glycol methyl ether) method to prepare the precursor solution. First, dissolve lead acetate in ethylene glycol methyl ether and reflux at 110 °C for 2 h. At the same time, dissolve zirconium propoxide in ethylene glycol methyl ether and reflux at 110 °C for 2 h. Then mix the two solutions evenly, add acetylacetone and formamide, and then stir at 80 °C for 1 h to finally obtain a PbZrO3 precursor solution with a concentration of 0.4 mol / L; (3-2) Preparation of PbZrO3 nanopowder: Put the PbZrO3 precursor solution obtained in step (3-1) into a constant temperature drying oven and dry it at 120 °C for about 72 h to obtain a xerogel. Then grind the xerogel in a mortar to obtain a coarse powder, and then calcine it at 650 °C for 4 h to obtain PbZrO3 nanopowder. Then ball mill it for 2 h and dry it to obtain PbZrO3 nanopowder with uniform dispersion and a particle size less than 50 nm; (3-3) Preparation of 0-3 type organic / inorganic composite mixed solution: Fill the PbZrO3 nanopowder prepared in step (3-2) into the P(VDF-TrFE-CFE) solution obtained in step (2-1) at 20 wt%, stir at room temperature for 12 h, and obtain a mixed solution of 0-3 type organic / inorganic composite film after ultrasonic dispersion.
[0039] (4) Spin-coat a 0-3 type organic / inorganic composite film on the surface of a pure P(VDF-TrFE-CFE) flexible piezoelectric polymer film for surface modification. The Young's modulus of the 0-3 type organic / inorganic composite film is about 12 - 18 GPa to match the organic / inorganic interface. Then, use a PDMS stamp to transfer the self-supporting antiferroelectric film onto the surface of the surface-modified flexible piezoelectric polymer film, and then heat to peel off the PDMS stamp to firmly bond the large-area self-supporting antiferroelectric film to the flexible piezoelectric polymer film.
[0040] (4-1) Spin-coat a 0-3 type organic / inorganic composite film on the surface of the pure P(VDF-TrFE-CFE) flexible piezoelectric polymer film obtained in step (2): Spin-coat the mixed solution of the 0-3 type organic / inorganic composite film at a speed of 600 rpm for 5 s, then spin-coat at a speed of 6000 rpm for 30 s, and then place it in an oven at 70 °C to dry for 20 min, and then place it in a vacuum oven at 120 °C to dry for 1 h to further enhance the bonding force between the P(VDF-TrFE-CFE) flexible piezoelectric polymer film and the 0-3 type organic / inorganic composite film; (4-2) Transfer the self-supporting antiferroelectric film using a PDMS stamp: Transfer the self-supporting PbZrO3 antiferroelectric film onto the surface of the surface-modified flexible piezoelectric polymer film to form a composite film structure of "P(VDF-TrFE-CFE) / 0-3 type composite film / PbZrO3 film", clamp it with PDMS, and then put it into a hot pressing fixture and hot press it in a vacuum oven at 150 °C for 20 min. The pressure of the fixture is 3 Pa, and the vacuum degree of the vacuum oven is maintained at 0.8 Pa.
[0041] (5) Spin-coat a layer of the mixed solution of the 0-3 type organic / inorganic composite film on the PbZrO3 surface of the composite film obtained in the previous step, and then prepare a composite film with a sandwich structure by the same hot pressing composite method.
[0042] (5-1) Spin-coat a layer of the mixed solution of the 0-3 type organic / inorganic composite film prepared in step (3) on the PbZrO3 surface of the "P(VDF-TrFE-CFE) / 0-3 type composite film / PbZrO3 film" composite film, spin-coat at a speed of 500 rpm for 3 s, then spin-coat at a speed of 4000 rpm for 20 s, and then place the composite film under the same conditions as in step (4-1) for drying and curing; Preparation of (5-2) sandwich-structured composite film: Cover the surface of the composite film obtained in step (5-1) with another layer of P(VDF-TrFE-CFE) flexible piezoelectric polymer film, and perform hot pressing again under the same hot pressing composite conditions as in step (4-2) to form a composite film with a "P(VDF-TrFE-CFE) / 0-3 type composite film / PbZrO3 film / 0-3 type composite film / P(VDF-TrFE-CFE)" sandwich structure, with a thickness of about 40 μm, as Figure 2 shown.
[0043] (6) Deposit a patterned metal electrode Au on the upper and lower surfaces of the composite film obtained in step (5-2) by using physical vapor deposition technology combined with a stainless steel mask, and obtain a flexible driving device with a sandwich structure after cutting.
[0044] (6-1) Deposition of metal electrode Au: Place the stainless steel mask on the surface of the composite film. There is a square electrode array with a side length of 1 cm on the stainless steel mask. Use the method of DC magnetron sputtering to deposit Au film as the top and bottom electrodes. The sputtering power is 70 W, the sputtering time is 1000 s, and the thickness of the Au film is about 100 nm; (6-2) Obtain a flexible driving device with a sandwich structure after cutting: Cut and divide the composite film with electrodes grown on the upper and lower surfaces with scissors, and lead copper wires to the upper and lower electrodes with silver paste to prepare a flexible driving device with a sandwich structure.
[0045] For the "P(VDF-TrFE-CFE) / 0-3 type composite film / PbZrO3 film / 0-3 type composite film / P(VDF-TrFE-CFE)" composite film obtained in this case, when an electric field of 150 MV / m is applied, an electrostrain of up to -8.3% is generated ( Figure 3 ), and after 1000 bends, an electrostrain of -7% can still be maintained ( Figure 4 ).
[0046] Example 2: Preparation of Pb 0.97 La 0.02 (Zr 0.95 Ti 0.05 )O3 / P(VDF-TrFE) flexible driving device (1) Step 1: Use the sacrificial layer method to prepare Pb 0.97 La 0.02 (Zr 0.95 Ti 0.05 )O3 (hereinafter referred to as PLZT) self-supporting antiferroelectric film.
[0047] (1-1) Pretreatment of the substrate: The SrTiO3 substrate was successively placed in acetone, alcohol, and water, ultrasonically cleaned for 10 minutes each, and dried with dry nitrogen to ensure that the substrate surface was clean and dust-free. (1-2) Deposition of the sacrificial layer: The sacrificial layer La 0.7 Sr 0.3 MnO3 was deposited on the substrate by magnetron sputtering. The radio frequency output power was 400 W, the sputtering temperature was 600 °C, the oxygen pressure was 0.4 Pa, the deposition time was 1200 s, and the growth thickness was about 30 nm. (1-3) Deposition of the PLZT thin film: The PLZT thin film was deposited on the sacrificial layer by radio frequency magnetron sputtering. The sputtering power was 150 W, the substrate temperature was 575 °C, the working gas Ar / O2 = 5 / 1, the working pressure was 2 Pa, and an antiferroelectric thin film with a thickness of 100 - 400 nm was prepared by controlling the growth time. The Young's modulus was about 55 - 70 GPa. (1-4) Obtaining a self-supporting PLZT thin film: The PDMS stamp was attached to the surface of the antiferroelectric thin film and immersed in a mixed etching solution of hydrochloric acid and potassium iodide at 50 °C for 12 h to remove the sacrificial layer. After La 0.7 Sr 0.3 MnO3 was dissolved, the PDMS stamp carried the antiferroelectric thin film and naturally detached from the substrate.
[0048] (2) Step two: Prepare a P(VDF-TrFE) flexible piezoelectric polymer thin film by the doctor blade method to obtain a flexible piezoelectric polymer thin film with a thickness of about 20 μm.
[0049] (2-1) Preparation of the P(VDF-TrFE) solution: Weigh commercial P(VDF-TrFE) particles and put them into the N,N-dimethylformamide (DMF) solvent, stir and dissolve for 12 h to fully dissolve P(VDF-TrFE) in the solvent, forming a uniform and stable solution with a concentration of 0.1 g / ml. The stirring speed was 120 rpm to avoid introducing too many bubbles. (2-2) Preparation of the flexible polymer film by the doctor blade method: Adjust the height of the doctor blade to 40 μm. At room temperature, pour the P(VDF-TrFE) solution obtained in step (2-1) evenly onto a 15 cm × 10 cm glass plate. The speed of the doctor blade was 1 cm / s, and then it was dried at 70 °C for 20 minutes to remove most of the solvent. After the solvent had basically evaporated, the glass plate was transferred to an oven and dried at 135 °C for 1.5 h to completely evaporate the solvent. To improve the crystallinity, the temperature was raised to 152 °C and held for 0.5 h, and then quenched in deionized water at room temperature to obtain a P(VDF-TrFE) flexible piezoelectric polymer thin film with a thickness of about 20 μm. The Young's modulus was about 2.4 GPa.
[0050] (3) Step 3: Prepare PLZT nanoflour by sol-gel method, and then compound it with P(VDF-TrFE) solution to prepare a 0-3 type organic / inorganic composite mixed solution.
[0051] (3-1) Prepare the PLZT precursor solution: Prepare the precursor solution by the 2MOE (ethylene glycol methyl ether) method. First, dissolve lead acetate and lanthanum acetate in ethylene glycol methyl ether, reflux at 110 °C for 2 h. At the same time, dissolve zirconium propoxide and titanium isopropoxide in ethylene glycol methyl ether, reflux at 110 °C for 2 h. Then mix the two solutions evenly, add acetylacetone and formamide, and stir at 80 °C for 1 h to finally obtain a PLZT precursor solution with a concentration of 0.4 mol / L. (3-2) Prepare the obtained PLZT nanoflour: Put the PLZT precursor solution obtained in step (3-1) into a constant temperature drying oven and dry it at 120 °C for about 72 h to obtain a xerogel. Then grind the xerogel in a mortar to obtain a coarse powder, and then calcine it at 650 °C for 4 h to obtain PLZT nanoflour. Then ball mill it for 2 h and dry it to obtain PLZT nanoflour with uniform dispersion and a particle size less than 60 nm. (3-3) Prepare a 0-3 type organic / inorganic composite mixed solution: Then fill the PLZT nanoflour prepared in step (3-2) into the P(VDF-TrFE) solution obtained in step (2-1) at 18 wt%, and stir at room temperature for 12 h to obtain a mixed solution of 0-3 type organic / inorganic composite film.
[0052] (4) Spin-coat a 0-3 type organic / inorganic composite film (Young's modulus is about 18-24 GPa) on the surface of the pure P(VDF-TrFE) flexible piezoelectric polymer film for surface modification to match the organic / inorganic interface. Then use a PDMS stamp to transfer the self-supporting antiferroelectric film to the surface of the surface-modified P(VDF-TrFE) flexible piezoelectric polymer film, and then heat to peel off the PDMS stamp to firmly bond the large-area self-supporting antiferroelectric film and the flexible piezoelectric polymer film.
[0053] (4-1) Spin-coat a 0-3 type organic / inorganic composite film on the surface of the pure P(VDF-TrFE) flexible piezoelectric polymer film obtained in step (2): Spin-coat the mixed solution of the 0-3 type organic / inorganic composite film at a speed of 600 rpm for 5 s, then spin-coat at a speed of 6000 rpm for 30 s. Subsequently, place the composite film in an oven at 70 °C and dry it for 20 min, and then place it in a vacuum oven and dry it at 120 °C for 1 h. (4-2)Transfer of self-supporting antiferroelectric thin films using a PDMS stamp: Transfer the self-supporting PLZT antiferroelectric thin film onto the surface of a surface-modified PVDF-TrFE flexible piezoelectric polymer thin film to form a composite film structure of "P(VDF-TrFE) / 0-3 type composite thin film / PLZT thin film". Clamp it with PDMS, then place it in a hot pressing fixture and hot press it in a vacuum oven at 195 °C for 10 min. The fixture pressure is 1 Pa, and the vacuum degree of the vacuum oven is maintained at 0.1 Pa.
[0054] (5)Spin-coat a mixed solution of a 0-3 type organic / inorganic composite film on the PLZT surface of the composite film obtained in the previous step, and then prepare a composite film with a sandwich structure by the same hot pressing and composite method.
[0055] (5-1)Spin-coat a mixed solution of the 0-3 type organic / inorganic composite film prepared in step (3) on the PLZT surface of the "P(VDF-TrFE) / 0-3 type composite thin film / PLZT thin film" composite film. Spin-coat it at a speed of 500 rpm for 3 s, then spin-coat it at a speed of 4000 rpm for 20 s. Subsequently, place the composite film in the same conditions as in step (4-1) for drying and curing; (5-2)Preparation of the sandwich structure composite film: Cover the surface of the composite film obtained in step (5-1) with another layer of P(VDF-TrFE) flexible piezoelectric polymer film, and hot press it again under the same hot pressing and composite conditions as in step (4-2) to form a composite film with a "P(VDF-TrFE) / 0-3 type composite thin film / PLZT thin film / 0-3 type composite thin film / P(VDF-TrFE)" sandwich structure, with a thickness of about 40 μm.
[0056] (6)Deposit a patterned metal electrode Pt on the upper and lower surfaces of the composite film obtained in step (5-2) using physical vapor deposition technology combined with a stainless steel mask plate. After cutting, a flexible driving device with a sandwich structure is obtained.
[0057] (6-1)Deposit the metal electrode Au: Place the stainless steel mask plate on the surface of the composite film. The stainless steel mask plate has a square electrode array with a side length of 1 cm. Use the method of DC magnetron sputtering to deposit an Au thin film as the top and bottom electrodes. The sputtering power is 70 W, the sputtering time is 1000 s, and the thickness of the Au thin film is about 100 nm; (6-2)Obtain a flexible driving device with a sandwich structure after cutting: Cut and divide the composite film with electrodes grown on the upper and lower surfaces with scissors, and lead copper wires to the upper and lower electrodes with silver paste to prepare a flexible driving device with a sandwich structure.
[0058] The "P(VDF-TrFE) / 0-3 composite film / PLZT film / 0-3 composite film / PVDF-TrFE" composite film obtained in this case generates an electrostrictive strain as low as -6.1% when an electric field of 100 MV / m is applied, and can still maintain an electrostrictive strain of > -5% after multiple bends.
Claims
1. A large strain flexible ferroelectric composite film, characterized in that: It includes a flexible piezoelectric polymer film, a 0-3 type organic / inorganic composite film, an antiferroelectric film, a 0-3 type organic / inorganic composite film and a flexible piezoelectric polymer film which are stacked in sequence; wherein the flexible piezoelectric polymer film is a film formed by a relaxor ferroelectric polymer, the antiferroelectric film is a film formed by an antiferroelectric material, and the 0-3 type organic / inorganic composite film is a film formed by a composite of the relaxor ferroelectric polymer and the antiferroelectric material.
2. The large strain flexible ferroelectric composite film according to claim 1, characterized in that: The relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is PbZrO3.
3. The large strain flexible ferroelectric composite film according to claim 1, characterized in that: The relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3.
4. The large strain flexible ferroelectric composite film according to claim 1, characterized in that: The relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the antiferroelectric material is La-doped Pb(Zr,Ti)O3; or, the relaxor ferroelectric polymer is P(VDF-TrFE), and the antiferroelectric material is PbZrO3.
5. The large strain flexible ferroelectric composite film according to claim 1, characterized in that: The thicknesses of the flexible piezoelectric polymer film, the 0-3 type organic / inorganic composite film and the antiferroelectric film are 10-30 μm, 30-100 nm and 100-400 nm respectively.
6. The method for preparing a large strain flexible ferroelectric composite film according to any one of claims 1 to 5, characterized in that: include: S1, prepare the self-supporting antiferroelectric film by sacrificial layer method and transfer the antiferroelectric film to the PDMS stamp; S2, preparation of flexible piezoelectric polymer films by scraping film method; S3, preparing a 0-3 type organic / inorganic composite film by spin coating on the surface of the flexible piezoelectric polymer film, transferring the antiferroelectric film to the surface of the 0-3 type organic / inorganic composite film by using a PDMS stamp, heating and peeling off the PDMS stamp, and hot pressing; S4, a 0-3 type organic / inorganic composite film is prepared by spin coating on the surface of the antiferroelectric film obtained in S3, and a flexible piezoelectric polymer film is prepared by a scraping method, and hot pressing is performed to obtain a large strain flexible ferroelectric composite film.
7. The method for preparing a large strain flexible ferroelectric composite film according to claim 6, characterized in that: S1 specifically includes: Depositing a sacrificial layer on the substrate using a pulsed laser deposition method; Depositing an antiferroelectric thin film on the sacrificial layer using a pulsed laser deposition method; The PDMS stamp is attached to the surface of the antiferroelectric film, and the sacrificial layer is removed by wet etching, so that the PDMS stamp carries the antiferroelectric film away from the substrate.
8. The method for preparing a large-strain flexible ferroelectric composite film according to claim 6, characterized in that: In S3 and S4, the preparation method of the 0-3 type organic / inorganic composite film is: prepare a solution of a relaxor ferroelectric polymer, add nanopowder of an antiferroelectric material to the solution of the relaxor ferroelectric polymer, stir, and ultrasonically disperse to obtain a 0-3 type organic / inorganic composite mixed solution; spin-coat the 0-3 type organic / inorganic composite mixed solution on the surface of a flexible piezoelectric polymer film or the surface of an antiferroelectric film to prepare a 0-3 type organic / inorganic composite film.
9. The method for preparing a large strain flexible ferroelectric composite film according to claim 6, characterized in that: In S3 and S4, the hot pressing conditions are: temperature of 150-200°C, pressure of 1-3 Pa, and vacuum degree of 0.1-1 Pa.
10. An electrostrictor, characterized in that: The invention comprises an electrostrictive material, wherein the electrostrictive material is the large-strain flexible ferroelectric composite film according to any one of claims 1 to 5, and a metal electrode is deposited on the outer side of the flexible piezoelectric polymer film in the large-strain flexible ferroelectric composite film.